2023
DOI: 10.3389/fnmol.2023.1224964
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of PGC-1α-mediated mitochondrial biogenesis in cerebral ischemia–reperfusion injury

Abstract: Cerebral ischemia–reperfusion injury (CIRI) is a series of cascade reactions that occur after blood flow recanalization in the ischemic zone in patients with cerebral infarction, causing an imbalance in intracellular homeostasis through multiple pathologies such as increased oxygen free radicals, inflammatory response, calcium overload, and impaired energy metabolism, leading to mitochondrial dysfunction and ultimately apoptosis. Rescue of reversibly damaged neurons in the ischemic hemispheric zone is the key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Upregulated NRF1 is associated with ameliorated depressive-like behaviors and improved cognitive dysfunctions in electroacupuncture-treated mice with post-stroke depression (Xia et al 2017 ). Molecularly, the main regulator of mitochondrial biogenesis PGC-1α improved mitochondrial function by activating its downstream genes NRF1 and TFAM, thereby remitting cerebral ischemia–reperfusion injury (Yuan et al 2023 ). More importantly, compelling evidence elicited that CAT enhanced mitochondrial biogenesis, evidenced by elevations in the expression of PGC-1α, NRF1, and TFAM (Xu et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Upregulated NRF1 is associated with ameliorated depressive-like behaviors and improved cognitive dysfunctions in electroacupuncture-treated mice with post-stroke depression (Xia et al 2017 ). Molecularly, the main regulator of mitochondrial biogenesis PGC-1α improved mitochondrial function by activating its downstream genes NRF1 and TFAM, thereby remitting cerebral ischemia–reperfusion injury (Yuan et al 2023 ). More importantly, compelling evidence elicited that CAT enhanced mitochondrial biogenesis, evidenced by elevations in the expression of PGC-1α, NRF1, and TFAM (Xu et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 5 Calcium overload plays a crucial role in the process of CIRI and triggers ischemic cascade reactions, which leads to irreversible neuronal damage. 53 , 54 Previous studies have shown that the occurrence of neurological diseases is related to intracellular calcium homeostasis disorders. 50 , 55 PKA plays a crucial role in the calcium signalling pathway of neurological diseases, and the activation of cAMP/PKA signalling pathway in the striatum is highly correlated with the loss of dopaminergic neurons in PD rats.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently a lack of effective treatment methods for ischemic stroke, an effective approach after cerebrovascular embolism in clinical practice is timely thrombolysis or endovascular intervention, intended to restore blood perfusion in the ischemic area; yet at the same time it can induce ischemia-reperfusion injury, which leads to brain damage both in the ischemic core and penumbra area. an ischemic stroke consists of two related pathological injury processes: Primary ischemia-induced brain injury and secondary ischemia reperfusion injury (3). a study has shown that neurons in the ischemic penumbra may undergo apoptosis hours or days after ischemia and alleviating ischemia reperfusion injury is an achievable therapeutic goal in the early intervention of ischemic stroke aimed at limiting the amount of infarction (4).…”
Section: Introductionmentioning
confidence: 99%